Eyes on hold: motion task difficulty jointly delays microsaccade and pupil responses - Rania Ezzo; Bogeng Song; Bas Rokers; Marisa Carrasco (Scientific Reports)
Abstract Microsaccades and pupil dynamics exhibit canonical temporal profiles, providing insights into perceptual and cognitive processes. Microsaccades are typically suppressed with respect to expected stimulus onset and followed by a rebound to baseline rates. Here, we investigated whether and how the temporal dynamics of microsaccades and pupil dilation vary with task difficulty for a motion perception task. We hypothesized that difficulty jointly delays the rebound of microsaccade rates and the time of peak pupil dilation when discriminating motion direction. Human observers discriminated motion direction (clockwise or counterclockwise) in a briefly presented perifoveal drifting stimulus, which varied according to two ‘easy’ vs ‘hard’ difficulty manipulations –cardinal vs oblique motion directions, and large vs small tilt offsets from the discriminated direction. We found that (1) increased task difficulty strengthened and prolonged microsaccade inhibition resulting in delayed rebounds, (2) peak pupillary responses were both larger in amplitude and delayed for more difficult conditions, (3) discrimination response time correlated with microsaccade rebounds and peak pupillary responses. We conclude that the delays in these microsaccade rebound and pupil responses are due to a prolonged period of sensory evidence accumulation, and that their correlated temporal dynamics support a shared neural mechanism underlying both pupil and microsaccade responses.